Fabrication Du Savon Kabakrou Et Ses Conséquences Sur Les Acteurs Principaux De Gbintou Dans La Commune De Bouaké (Côte d’Ivoire) - André-Nestor, Yedagne De (European Scientific Journal, ESJ, 2016)
For the inhabitants of Gbintou (a district of the town of Bouaké), manufacture traditional soap, kabakrou, is the main economic activity of survival. In fact, this activity is a source of wealth, but a risky source of wealth. Indeed, the actors face many difficulties in the manufacturing process (raw material supply, health difficulties) the point of wanting to simply abandon the trade. The implementation of the socio-anthropological functionalist method and the study of this activity helped to understand that apart from raw material acquisition difficulties and illnesses it generates (contact urticaria, infections broncho lung), the company suffers from a lack of garish consequent functional organization and sanitary hygiene. Thus, it is desirable to set up an association or cooperative well equipped to train and organize stakeholders and better manage the entire manufacturing process.